Masalah Yang Dihadapi Dunia Pendidikan Dengan Tutorial Online: Sebuah Short Review - Yustika, Gaung Perwira; Subagyo, Adam; Iswati, Sri (Tadbir : Jurnal Studi Manajemen Pendidikan, 2019)
Despite the many benefits of virtual distance learning (online), in its course distance education still has many problems. Educators and managers try to continue to improve the quality of teaching and the struggle of online class facilitators to improve the quality of distance education, but it is discovered that online class data is not the student's first choice. The results show that one of the problems in online education comes from the drop out / failure rate of students which is more common in virtual classrooms compared to traditional classes. Other studies reveal several factors such as the time needed to complete the module, lack of understanding of the context in the subject matter, problems with software accessibility, availability of reliable teachers, lack of support from the government and other reasons can create a decrease in motivation and a less conducive learning atmosphere.